Effects of using an abdominal simulator to develop palpatory competencies in 3rd year medical students - Robert M. Hamm; David M. Kelley; Jose A. Medina; Noreen S. Syed; Geraint A. Harris; Frank J. Papa (BMC Medical Education, 2022)
Abstract Background Medical school faculty are hard pressed to provide clerkship students with sufficient opportunity to develop and practice their capacity to perform a competent clinical examination, including the palpatory examination of the abdomen. We evaluated the impact of training with an abdominal simulator, AbSim, designed to monitor the depth, location, and thoroughness of their palpation and to provide concurrent and summative feedback regarding their performance. Methods All third-year medical students were given the opportunity to develop their palpatory skills with the AbSim simulator during the family medicine rotation. The performance of those who studied with the simulator was measured by its sensors, before and after a training session that included visual feedback regarding the depth and coverage of the student’s manual pressure. Additionally, all students reported their confidence in their evolving abdominal palpation skills at the beginning and end of the rotation. Results 119 (86.9%) of 137 students filled out the initial questionnaire, and 73 (61.3%) studied with the abdominal simulator. The training produced a highly significant improvement in their overall performance (4 measures, p’s < 0.001). Pre-training performance (depth calibration and thoroughness of coverage) was not related to the number of months of previous clinical rotations nor to previous internal medicine or surgery rotations. There was little relation between students’ confidence in their abdominal examination skills and objective measures of their palpatory performance; however, students who chose the training started with less confidence, and became more confident after training. Conclusions Guided abdominal simulator practice increased medical students’ capacity to perform an abdominal examination with more appropriate depth and thoroughness of palpation. Interpretation of changes in confidence are uncertain, because confidence was unrelated to objectively measured performance. However, students with low initial confidence in their abdominal examination seemed to be more likely to choose to study with the abdominal simulator.